Effects of Inter-Stimulus Interval on Speech-Evoked Frequency-Following Response in Elderly Adults - Liu, Dongxin; Hu, Jiong; Dong, Ruijuan; Chen, Jing; Musacchia, Gabriella; Wang, Shuo (Frontiers in Aging Neuroscience, 2018)
[Background] Speech auditory brainstem response consists of two main components, one is transient response and the other is frequency-following response. [Objective] This study was designed to examine the effects of aging and inter-stimulus intervals on lexical tone evoked frequency-following response in Chinese elderly adults. [Material and Methods] Twenty-three normal hearing subjects were recruited in our study, including eleven young adult subjects and eleven elderly subjects. The Intelligent Hearing Systems Smart EP evoked potential system was used to record FFR. The synthesized falling tone /yi/ was used as the stimulus. Two indices, pitch correlation coefficients and pitch strength, were used to quantify the FFR responses. One-way analysis of variance was used to analyze the significant differences. [Results] Significant differences of both pitch correlation coefficients and pitch strength were found between the young group and the elderly group. There was no significant difference of both pitch correlation coefficients and pitch strength when using different inter-stimulus intervals. [Conclusions] In comparison with young adults, elderly adults have degraded FFR in the pitch correlation and pitch strength. In addition, an inter-stimulus intervals of as low as 40 ms appear be sufficient and effective to record FFR for elderly adults.